Kekerasan Seksual terhadap Perempuan dalam Konflik Bersenjata di Tigray Ethiopia dalam Kajian Hukum Internasional - Natalia Yeti Puspita; Natasya Fahira; Revin Andhika (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2022)
Sexual violence against women is often used as a military strategy to subdue the enemy. Sexual violence against women can result in the impurity of certain ethnicities due to rape and pregnancy and the humiliation of opponents. This happened in the armed conflict in Tigray-Ethiopia in 2020. This article analyzes the international legal protection of women from sexual violence in armed conflict in Tigray. The discussion shows that the armed conflict between the Central Government of Ethiopia and the Tigray People's Liberation Front (TPLF) in 2020 can be categorized as a non-international armed conflict. The absence of preventive and repressive efforts by the two warring parties, especially the central government of Ethiopia, regarding the sexual violence against Tigray women, shows that there is no legal protection for women in armed conflicts. This violates Article 27 of the 4th Geneva Convention of 1949, Article 4 paragraph (2) letter e of Additional Protocol II of 1977, and violates the principles of non-reciprocity, military necessity, distinction, proportionality, and humanity. In addition, sexual violence against women during armed conflict is an international crime under the Rome Statute. Ethiopia is a party to the 1949 Geneva Conventions and the 1977 Additional Protocol and can therefore be held accountable.